The Extent of future foreseeing skills inclination in the content of artificial intelligence course for the secondary stage in Kingdom of Saudi Arabia - Alarawi, Amirah Saleh; Almohamade, Najwa Atian (Journal of Curriculum and Teaching Methodology, 2025)
The study aimed to determine the degree to which future foreseeing skills are included in the content of the Artificial Intelligence course for the secondary stage in the Kingdom of Saudi Arabia. To achieve the objectives of the study, the two researchers followed the descriptive analytical approach using the content analysis method to suit the nature of the research. The two researchers analyzed the content of the artificial intelligence course taught by male and female students in the third year of secondary school at the secondary level (computer science and engineering track), For the edition of the academic year 1445 AH- corresponding to 2023 AD, using a content analysis card containing (4) main skills that included (27) indicators to measure the degree of inclusion, distributed into four main skills for anticipating the future skills, which are: the skill of stimulating the imagination, the skill Solving future problems, t, the skill of decision-making, the skill of comparing different opinions.The results showed that the inclusion of future foreseeing skills in the Artificial Intelligence curriculum for the secondary stage (computer science and engineering track) in the Kingdom of Saudi Arabia was (52.29%) with a moderate degree of inclusion. In light of the results of the study, the two researchers recommended developing the content of the Artificial Intelligence curriculum in the Kingdom of Saudi Arabia. Saudi Arabia in light of the skills of anticipating the future, given the importance of these skills as they contribute to making the individual adapt to his present and ready to design and create his future. The future belongs to those who prepare for it.
Keywords: Artificial Intelligence; Future Foreseeing Skills; Secondary Stage; Stimulating Imagination Skills; Solving Future Problems Skills; Decision Making Skills; Comparing Different Opinions Skills